2020
DOI: 10.1007/s11626-020-00515-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Noonan syndrome-specific human-induced pluripotent stem cells under serum-, feeder-, and integration-free conditions

Abstract: Noonan syndrome is an autosomal dominant developmental disorder. Although it is relatively common, and its phenotypical variability is well documented, its pathophysiology is not fully understood. Previously, with the aim of revealing the pathogenesis of genetic disorders, we reported the induction of cleidocranial dysplasia-specific human-induced pluripotent stem cells (hiPSCs) from patient’s dental pulp cells (DPCs) under serum-free, feeder-free, and integration-free conditions. Notably, these cells showed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Establishment and maintenance of CS-iPSC under feeder- and serum-free conditions. The establishment of CS-iPSCs from CS-PBMCs (Takahashi et al , 2007 ) was performed according to a method previously reported under feeder- and serum-free conditions (Hamada et al , 2020a ). After culturing PBMCs in serum-free RD6F medium (Sato et al , 1987 ) supplemented with IL-2 (CELEUK, Takeda Pharm., Osaka, Japan) for 6 d, the cells were infected with Sendai virus vector at MOI = 6 and reseeded on Laminin-E8 in serum-free hESF6 medium supplemented with FGF2, heparin, and activin A (Yamasaki et al , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishment and maintenance of CS-iPSC under feeder- and serum-free conditions. The establishment of CS-iPSCs from CS-PBMCs (Takahashi et al , 2007 ) was performed according to a method previously reported under feeder- and serum-free conditions (Hamada et al , 2020a ). After culturing PBMCs in serum-free RD6F medium (Sato et al , 1987 ) supplemented with IL-2 (CELEUK, Takeda Pharm., Osaka, Japan) for 6 d, the cells were infected with Sendai virus vector at MOI = 6 and reseeded on Laminin-E8 in serum-free hESF6 medium supplemented with FGF2, heparin, and activin A (Yamasaki et al , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the field of oncology, the use of iPSCs with the genetic backgrounds of patients with hereditary tumor syndromes may lead to the elucidation of not only the development of hereditary tumors but also the mechanism of somatic carcinogenesis. We have previously reported the induction of iPSCs from dental pulp and peripheral blood mononuclear cells (PBMCs) of patients with several genetic disorders under feeder-, serum-free culture conditions (Yamasaki et al , 2014 ; Hamada et al , 2020a , 2020b ). In the present study, we found two novel PTEN exon 8 mutations in the same allele in a Japanese CS patient.…”
Section: Introductionmentioning
confidence: 99%
“…As human model for NS and NSML, patient derived iPSCs containing SHP2 variants, are used to study cardiac, neuronal and hematopoietic defects (Carvajal-Vergara et al, 2010;Hamada et al, 2020;Li et al, 2019;Meier et al, 2021;Mulero-Navarro et al, 2015;Pearson et al, 2020). The first iPSCs with SHP2 variants were derived more than a decade ago from skin fibroblasts of two NSML patients carrying the SHP2-T468M mutation (Carvajal-Vergara et al, 2010).…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Moreover, efficient and low-cost culture substrates that facilitate the derivation and large-scale expansion of quality-controlled hPSCs without direct or indirect exposure to xenobiotics are lacking. Although various xeno-free hPSC culture substrates have been developed and are commercially available, most of these require the inclusion of particular recombinant human extracellular matrix (ECM) proteins 5 , 6 like vitronectin, laminins, or their fragments 7 9 . These substrates require a laborious and time consuming coating, are thermosensitive and expensive, hindering the cost-effective scale-up of hPSC production for clinical and industrial applications.…”
Section: Introductionmentioning
confidence: 99%